To Perform Thrombolysis or Not: A Case of Acute Pancreatitis Presenting with Chest Pain and Transient Left Bundle Branch Block - S. Ullah; S. Mehmood; H. A. Chatha; A. Mahmood (Case Reports in Medicine)
A suspected case of acute coronary syndrome presented with new-onset left bundle branch and first-degree heart blocks. The decision to thrombolyse was reverted as ECG changes proved to be transient within fifteen minutes of presentation. Later on the patient was diagnosed with acute pancreatitis based on laboratory results of serum amylase, confirmed on radiological investigations.